2018
DOI: 10.1186/s12883-017-0998-8
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging features of benign retroperitoneal paragangliomas and schwannomas

Abstract: BackgroundTo determine whether MRI feature analysis can differentiate benign retroperitoneal extra-adrenal paragangliomas and schwannomas.MethodsThe MRI features of 50 patients with confirmed benign retroperitoneal extra-adrenal paragangliomas and schwannomas were retrospectively reviewed by two radiologists blinded to the histopathologic diagnosis. These features were compared between two types of tumours by use of the Mann-Whitney test and binary logistic regression. The patients’ clinical characteristics we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 32 publications
1
66
0
Order By: Relevance
“…Schwannomas usually appear as a well-circumscribed, homogenous, and round or oval lesion, with slight enhancement on the CT scan with cystic degeneration or calcification [10]. In one study, it was found that the combination of necrosis with a minimal degree of tumor enhancement in the arterial phase of the CT scan increased the probability of ruling out schwannoma [11]. Furthermore, the schwannomas on MRI appear as a well-circumscribed mass with cystic degenerative changes with low signal intensity on T1-weighted images and heterogeneous high signal intensity on T2-weighted images.…”
Section: Discussionmentioning
confidence: 99%
“…Schwannomas usually appear as a well-circumscribed, homogenous, and round or oval lesion, with slight enhancement on the CT scan with cystic degeneration or calcification [10]. In one study, it was found that the combination of necrosis with a minimal degree of tumor enhancement in the arterial phase of the CT scan increased the probability of ruling out schwannoma [11]. Furthermore, the schwannomas on MRI appear as a well-circumscribed mass with cystic degenerative changes with low signal intensity on T1-weighted images and heterogeneous high signal intensity on T2-weighted images.…”
Section: Discussionmentioning
confidence: 99%
“…Retroperitoneal paragangliomas are rare tumours arising from chromaffin cells along the autonomic nervous system, with an estimated incidence of 2-8 per million, 1 accounting for 1-3% of retroperitoneal tumors. 3 Those paragangliomas arising from the medulla are known as pheochromocytomas, which comprise nearly 70% of such cases. 4 Paragangliomas are known to occur in various locations in the body such as the head and neck, thorax and abdomen.…”
Section: Discussionmentioning
confidence: 99%
“…On T1 weighted images, tumours appear similar to liver and muscle with an enhancement observed in T2 and diffusion-weighted image, confirming the diagnosis. 3 Nuclear imaging in the form of I123 MIBG and F18-fluorodopa positron emission tomography (PET) is also useful in the diagnosis of these enigmatic tumours. 123 MIBG has a sensitivity of 92-98% for non-metastatic tumours and 57-79% for detecting metastases.…”
Section: Discussionmentioning
confidence: 99%
“…All of the studies used an enzyme-like immunosorbent assay (ELISA) as their main experimental approach to detect Aβ. Most of the studies (5/7) demonstrated increased levels of Aβ42 in AD patients [ 52 , 53 , 54 , 55 , 56 ] while the others (2/7) showed undetectable or unchanged Aβ42 levels [ 42 , 57 ]. With the exception of a relatively larger study by Bermejo-Pareja et al [ 55 ], including 70 AD patients and 56 healthy volunteers serving as the study’s controls, the remaining studies reported results on much smaller cohorts ranging from 7–28 AD patients and 7–38 healthy controls.…”
Section: Salivamentioning
confidence: 99%
“…More specifically, Sabbagh et al [ 52 ] recruited 15 AD patients (7 males, mean age: 77.8 years, mean mini-mental state examination (MMSE) score 19.0) and 7 normal controls (2 males, mean age: 60.4 years, mean MMSE 29.0) and demonstrated significantly higher salivary Aβ42 in AD patients than in controls (51.7 ± 1.6 pg/mL for AD and 21.1 ± 0.3 pg/mL for controls, p < 0.001). Participants were enrolled as mild and moderate AD according to the AD criteria established by the National Institute on Aging and the Alzheimer’s Association (NIA-AA) [ 79 ].…”
Section: Salivamentioning
confidence: 99%